2001 International Semiconductor Conference. CAS 2001 Proceedings (Cat. No.01TH8547)
DOI: 10.1109/smicnd.2001.967428
|View full text |Cite
|
Sign up to set email alerts
|

A global survey on short range low power wireless data transmission architectures for ISM applications

Abstract: Different short range low power wireless data transmission systems for ISM (Industrial Scientific and Medical) applications are compared with respect to their performances (power consumption, distance range, architecture well suited to integration, etc). An original solution, specifically dedicated to applications for which the power consumption has to be minimized on the data carrier side of the wireless link, is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The conventional quenching operation is realized by changing the gate or the base bias-voltage [2] [3]. But in case of this MSW oscillator, it is confirmed that the approach leads to the unstable oscillation.…”
Section: Configuration Of Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional quenching operation is realized by changing the gate or the base bias-voltage [2] [3]. But in case of this MSW oscillator, it is confirmed that the approach leads to the unstable oscillation.…”
Section: Configuration Of Circuitmentioning
confidence: 99%
“…The demodulated signal can be obtained from the change of the evolution of the oscillation waveform [1]. Some researches on the super-regenerative detection in microwave region have already been performed [2] [3]. But they are on the operation of a constant frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the core of the oscillator often requires a simple amplifier to compensate resonator losses and could operate at low bias current. However in narrow band communications, such architecture suffers from a lack of frequency selectivity which is always many times larger than the maximum data rates [5]. This excessive reception bandwidth makes the receiver more sensitive to noise and interference compared to other systems.…”
Section: The Interest Of Super-regenerative Architecture For Impumentioning
confidence: 99%
“…Next, at time tb, detector comes back in a stable mode where S is positive: oscillations are damped until next input signal sample phase. (5) and po (t)=e tb This expression shows that ifpo equal p, the response of the super-regenerator could be considered as a simple linear amplifier with a gain equal to the product KOKrK. Next section deals with the optimization of these parameters and of the whole super-regenerative architecture in the presence of UWB input signal.…”
Section: Theory and Modelization Of Super-regenerative Detector mentioning
confidence: 99%
“…There is a significant amount of literature, such as [33,46,76,77,78] targeted at the reduction of communication energy of wireless sensor networks (WSNs) and the increase of system battery lifetime. However, interference robustness is not addressed that much even though communication in most WSNs takes place in the largely crowded ISM frequency bands [27].…”
Section: Chirped-lo Based Interference Robust Communication 41 Intromentioning
confidence: 99%